Nurses’ perception of organizational justice and its relationship to their workplace deviance - Hashish, Ebtsam Aly Abou (Nursing ethics, 2020)
Background:Today, healthcare organizations are challenged to retain nurses’ generation and to maintain justice that is a predictor of nurses’ behaviors in their work environment. Acquiring knowledge about the level of organizational justice and workplace deviance could help in identifying factors amenable for change that can make a difference in enhancing nurses’ dedication and loyalty to their organizations.Aim:The aim of this study was to investigate nurses’ perception of organisational justice and workplace deviance in their hospital, and to determine the relationship between perceived organisational justice and workplace deviance.Methods:A cross-sectional design was used with a convenient sample of all nurses (N = 400) who were working in inpatient care units at two Egyptian hospitals affiliated to the university and private health sectors in Alexandria governorate, Egypt. Organisational justice and workplace deviance questionnaires proved valid and reliable to measure studied variables. Descriptive analysis, Student’s t-test, Pearson correlation (r), and regression analysis (R2) were used for statistical analysis.Ethical considerations:This study was approved by the Ethics Committee at the Faculty of Nursing, Alexandria University. Informed consent, information confidentiality, and voluntary participation were guaranteed.Results:This study showed that overall nurses’ perceptions of organisational justice and workplace deviance are lower than the average. Organisational justice significantly related negatively to workplace deviance (r = −0.152, p = 0.002) and organisational justice as an independent variable contributed a significant predictive power of workplace deviance (R2 = 0.023).Conclusions:This study highlighted important implications for hospital and nurse managers to create and maintain a healthy and supportive work environment that promotes organisational justice and decreases workplace deviance. To achieve this, a culture of respectful communication, justice in policies, and a proper procedure for allocating resources, workload, and rewards systems is a must. Educational interventions to increase nurses’ awareness of workplace deviance and its potential consequences and coping strategies are imperative for the health of the nursing profession.